2015
DOI: 10.1002/bies.201500103
|View full text |Cite
|
Sign up to set email alerts
|

Insider trading: Extracellular matrix proteins and their non‐canonical intracellular roles

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Graphical AbstractIt is a given that ECM proteins function outside cells. We evaluate emerging data that implicate noncanonical roles in the cytoplasm or nucleus. We discuss the conceptual and experimental challenges that will need to be met to investigate this under-studied area of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 121 publications
(167 reference statements)
0
16
0
Order By: Relevance
“…It was also suggested that TRIP11 may play a specific role in secretion of extracellular matrix proteins [34]. Remarkably, disturbances in expression and secretion of ECM proteins contribute to the progression of renal and other cancers [17,35,36]. Thus, disturbed expression of TRIP11 might also contribute to alterations in ECM of renal tumours.…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that TRIP11 may play a specific role in secretion of extracellular matrix proteins [34]. Remarkably, disturbances in expression and secretion of ECM proteins contribute to the progression of renal and other cancers [17,35,36]. Thus, disturbed expression of TRIP11 might also contribute to alterations in ECM of renal tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the presence of cells and their abundant intracellular proteins can make it difficult to isolate the ECM as a discrete extracellular structure. Indeed, some ECM proteins have roles inside the cell as well as in the ECM 4 ; therefore, the efficient removal of intracellular proteins from cell-derived ECM is vital if the study of proteins within the ECM is not to be confused with their roles inside the cell. Secondly, cell-derived ECM is composed of many large, oligomeric proteins, which are often covalently cross-linked upon ECM assembly and are therefore insoluble in standard detergents.…”
Section: Introductionmentioning
confidence: 99%
“…Best known for their roles in the hydrolysis of otherwise proteolytically resistant ECM proteins, especially during normal and pathological tissue remodeling, these proteases have more recently become recognized as essential components of signal transduction pathways -mediating the presentation of extracellular ligands, availability of cell surface receptors, etc. -and even intracellular processes [3,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%